Accounting measurement of intangible assets (websites) within the framework of international financial reporting standards An applied study between a sample of Iraqi commercial banks) - Abdull, Athraa Yaseen; H, Abdullah, Salman (Journal of Economics and Administrative Sciences, 2020)
The websites over time have become one of the important tools for communication between individuals among themselves and between individuals and economic units, and they have emerged as one of the important intangible assets to achieve income, as they have become a competitive tool and a marketing outlet for these units and a main means of communication that it uses to exercise its various major activities and achieve potential economic benefits. Therefore, there was a need to measure and display the value of these sites in the financial statements as intangible assets. Accordingly, the purpose of the research was to determine the costs of the websites owned by the economic unit by way purchase and sites that were created internally and to determine an appropriate measurement model to evaluate and extinguish them, in addition to distinguishing between them and Traditional intangible assets such as (good well, brand, patent). The research problem was the failure of the Iraqi economic units in the research sample to follow the scientific and professional method of recognition and measurement of the websites they own as an intangible asset and determine their costs and evaluate them in a way that reflects the unit’s performance and value. The research field represents the Iraqi commercial banks listed in the Iraqi market for securities, as the research sample reached (five) banks: (the Gulf Commercial Bank, the South Islamic Bank for Investment and Finance, the Mosul Development and Investment Bank, the United Investment Bank and the Iraqi Investment Bank). On the analytical side of the research, the data obtained for the period extending from the date of ownership of the site and the year following it were relied on, in addition to the method of personal observation and interview and The research found that financial reporting on websites in the Iraqi economic units is still incomplete despite the issuance of IAS38 and local accounting rule No. 2 (intangible assets) issued by the Accounting and Auditing Standards Board in the Republic of Iraq regulating the accounting procedures for these sites as an asset Intangible, and the unified accounting system lacks accounting treatments in a manner that is consistent with the standards issued in this regard. The research found that there is a possibility to determine the costs of the websites that were created internally and to recognize them as an intangible asset with a good cost system that helps in determining their costs more accurately and enabling the economic unit to determine the direct and indirect costs of its formation. Accordingly, the research recommendations came with the necessity of making some adjustments to the local accounting base (2) (intangible assets) by aligning it with IAS38 (intangible assets) and the interpretation of the SIC32 (intangible assets - website costs), and work To include the unified accounting system and the accounting system for banks and insurance with accounting treatments and tabulations that clearly express the intangible assets in general and websites in particular.